Are there too few women presenting at emergency medicine conferences?. Issue 10 (17th August 2016) - Carley, Simon; Carden, Richard; Riley, Rebecca; May, Natalie; Hruska, Katrin; Beardsell, Iain; Johnston, Michelle; Body, Richard
Abstract : Introduction: There is a perception that women are under-represented as speakers at emergency medicine (EM) conferences. We aimed to evaluate the ratio of male to female speakers and the proportion of presenting time by gender at major international EM conferences. Methods: Conference programmes of the major English-speaking EM conferences occurring from 2014 to 2015 were obtained. The number of presentations, the gender of the speaker and the duration of each presentation were recorded. Results: We analysed eight major EM conferences. These included 2382 presentations, of which 29.9% (range 22.5%–40.9%) were given by women. In total, 56 104 min of presentations were analysed, of which 27.6% (range 21%–36.7%) were delivered by women. On average, presentations by women were 95 s shorter than presentations by men (23 vs 21 min 25 s). Conclusions: Male speakers exceed female speakers at major EM conferences. The reasons for this imbalance are likely complex and multifactorial and may reflect the gender imbalance within the specialty.